A regional view of the linkages between hydro-climaticchanges and deforestation in the Southern Amazon (2022)
ABSTRACT: In the last four decades, theSouthern Amazon (south of 8 S) has shown changesin the spatial and temporal patterns of itshydro-climatic components, leading todrier conditions. Due to climate and land-use changes, this region is considered asa zone under biophysical transition processes. Previous studies have documenteda complex interaction between climate anddeforestation either on a large-scale orbased on limited in situ data, typicallycovering the Brazilian Amazon. In thisstudy, we analyse the relationships between hydro-climate, the surface water-energy partitioning and an index of regional forest cover change for the period1981–2018. Additionally, we discretized three regions covering the Bolivian Ama-zon and the southern portions of the Peruvian and Brazilian Amazon due to theirdifferences in the evolution of land use. In the Bolivian region, a high ratio of for-est cover change, exceeding 40–50%, is related to a significant tendency to becomewater-limited. This change is associated with decreased rainfall, increased poten-tial evapotranspiration and decreased actual evapotranspiration. Regardless of theregion analysed, those that are characterized by a high ratio of forest cover change(>40–50%) show growing imbalance between increasing potential and decreasingactual evapotranspiration. However, in the Peruvian and Brazilian regions, hydro-climatic conditions remain energy-limited due to minor rainfall changes. Theobserved differences in surface water-energy partitioning behaviour evidence acomplex dependence of both sub-regional (i.e., land cover changes) and large-scale(i.e., strengthening of the Walker and Hadley circulations) conditions. Ourfindings indicate a clear link between hydro-climatic changes and deforestation,providing a new perspective on their spatial variability on a sub-regional scale.